Diagnostic value of sonographic signs in acute injury of anterior talofibular ligament - Meijun Zhou; Jialin Ye; Sushu Li; Wenhong Yi; Yu Wang; Jiangting Ji; Tianyue Wang; Yi Yin; Yanni He; Hongmei Liu (WFUMB Ultrasound Open)
Objectives: The present study aimed to determine the diagnostic value of sonographic signs in patients who have experienced an acute injury of the anterior talofibular ligament (ATFL), and provide diagnostic evidence for improving the classification of ATFL injuries. Methods: We retrospectively analyzed a total of 158 ATFL injuries, confirmed by surgery or magnetic resonance imaging (MRI), in 157 patients (one patient had bilateral ankle injury). A group of senior radiologists, along with two junior radiologists, identified the direct and indirect sonographic signs of ATFL injuries on ultrasound (US) images, and determined the ATFL injury classification. We then compared the diagnostic accuracy of the ATFL injury classifications, as well as the consistency of sonographic sign identification, between the senior radiologist group and the two junior radiologists. The sonographic signs identified by the senior radiologist group were used as the standard by which we analyzed the diagnostic efficacy of each sonographic sign for ATFL injury classification. Results: The diagnostic accuracy for complete ATFL tears was 88.5 % in the senior radiologist group, which was higher than that for the two junior radiologists (72.3 % and 67.7 %). Compared to the senior radiologist group, the consistency between the two junior radiologists in identifying all sonographic signs of ATFL injuries was low (kappa value < 0.75). Most complete tear, partial tear, and sprain/normal ATFL showed ligament thickening and were predominantly hypoechoic, but there were significant differences in ligament tension, clarity, and continuity (P < 0.05). The sensitivity of direct sonographic signs alone in the diagnosis of complete ATFL tears reached 100 %, and the positive predictive value, negative predictive value, and accuracy rate were all > 80 %. Direct sonographic signs were further combined with indirect sonographic signs to improve the diagnostic specificity and positive predictive value for the diagnosis of ATFL injuries. Conclusions: High-frequency US is the first choice for the diagnosis of ATFL injuries; however, radiologists with different levels of experience may classify ATFL injuries differently. Refined sonographic signs, especially ligament tension, clarity, and continuity, are helpful in the classification and diagnosis of ATFL injuries and provide guidance for the treatment and management of ankle injuries in clinical practice.